Tari Baris Teruna Batu di Desa Pakraman Teruna Blahbatuh Gianyar: Kajian Aksiologi Hindu - Ni Made Sukrawati; Wayan Paramartha; Ni Kadek Ayu Kristini Putri (Mudra Jurnal Seni Budaya, 2022)
Balinese dance is an important part of Balinese life that has been passed down since ancient times. The art of dance is an expression of the human soul which is poured through beautiful rhythmic movements and through the creation of taste and intention that is observed by the dance stylist. Balinese dances are generally classified into 3 groups, namely, Wali (sacred performing arts), Bebali (performing arts for ceremonies), and Balih-balihan (dance arts for the entertainment of visitors). The same is true for the Baris Teruna Batu dance, which has the same sacred position in comparison to other wali dances that have an important contribution in every movement and rhythm of the dancer's body in giving thanks to Ida Sang Hyang Widhi (God). In this study, the method used was a qualitative method, using an interpretive qualitative descriptive analysis. Furthermore, in analyzing the research data, a series of stages were carried out so that the results were logical, objective and empirical. The series of steps are as follows: reducing data, displaying data, verifying data and interpreting research data. The essence of this study found several value studies, namely, aesthetic values, educational values, and sacralization values. There are still numerous studies that need to be conducted with regard to the various aspects of the aforementioned baris dance. The sacredness and so many meanings contained in it make the Baris Teruna Batu dance still exist and develop to this day.